Implementation of Congregational-Based Financing through Qardul Hasan Contracts in Microbusiness Development: Case Study at BMT NU Branch in Sumenep City - Fauziyah, Hanifah; Khalida, Nur Diana; Firdaus, Jannatul; Najiatun, Najiatun (Masyarakat Ekonomi Syariah Bogor, 2025)
The article titled,